INKONSTITUSIONALITAS PEMBENTUKAN PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG NO. 2 TAHUN 2022 BERDASARKAN PUTUSAN MAHKAMAH KONSTITUSI NOMOR 91/PUU-XVIII/2020: Inconstitutionality of Formation of Government Regulation Substituting Law No. 2/2022 Based on Constitutional Court Decision Number 91/PUU-XVIII/2020 - Nyimas Reysandra Kinnary; Ali Rido (Faculty of Law, Universitas Trisakti, 2025)
This study discusses the issuance of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation, which sparked debates regarding the fulfillment of the